CREATION OF THE PLACE OF SPECIALISTS AND JOB IN THE TEXTILE INDUSTRY - Utayeva Feruza Kholmamatovna (Лучшие интеллектуальные исследования, 2024)
Abstract: This article examines the history of the textile industry, one of the most important branches of light industry. Since the textile industry does not have a large negative impact on the environment, it was in densely populated areas that textile factories were built. In particular, facilities were built near the residential area of Bukhara Textile Mill in the city of Bukhara on an area of 76 hectares, cotton yarn was developed in factories, many families got jobs. Abandoned and abandoned places were reclaimed and a large Bukhara textile factory was built. Factories adapted for production began to work, directly connecting the city with villages and districts. Under the leadership of the Ministry of Light Industry of Uzbekistan, cooperation has been established with textile factories in the regions of the republic.The article shows the aspects that served the development of the material needs of the population.